Corrigendum to 'Global Meat Consumption Trends and Local Deforestation in Madre de Dios: Assessing Land Use Changes and Other Environmental Impacts': [Procedia Engineering, Volume 118, 2015, Pages 630–638]. (2015) - Recanati, F.; Allievi, F.; Scaccabarozzi, G.; Espinosa, T.; Dotelli, G.; Saini, M.
Abstract : The authors regret: